2018
DOI: 10.1002/chem.201705577
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Glycerol as a Sustainable Solvent to Organolithium Chemistry: Ultrafast Chemoselective Addition of Aryllithium Reagents to Nitriles under Air and at Ambient Temperature

Abstract: Edging closer towards developing air and moisture compatible polar organometallic chemistry, the chemoselective and ultrafast addition of a range of aryllithium reagents to nitriles has been accomplished by using glycerol as a solvent, at ambient temperature in the presence of air, establishing a novel sustainable access to aromatic ketones. Addition reactions occur heterogeneously ("on glycerol conditions"), where the lack of solubility of the nitriles in glycerol and the ability of the latter to form strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Independent studies reported by Dilauro et al. and us have demonstrated that organolithium‐mediated organic reactions “on‐water” or “on‐glycerol” can be dramatically affected by the surface and the volume of the organic droplets formed by the water‐ or glycerol‐insoluble reagents involved in the process . These studies have confirmed that the yields of the reactions can be improved by employing vigorous stirring (vortex) to generate an emulsion of the organic reactants in aqueous media.…”
Section: Resultsmentioning
confidence: 99%
“…Independent studies reported by Dilauro et al. and us have demonstrated that organolithium‐mediated organic reactions “on‐water” or “on‐glycerol” can be dramatically affected by the surface and the volume of the organic droplets formed by the water‐ or glycerol‐insoluble reagents involved in the process . These studies have confirmed that the yields of the reactions can be improved by employing vigorous stirring (vortex) to generate an emulsion of the organic reactants in aqueous media.…”
Section: Resultsmentioning
confidence: 99%
“…Since recent reports have proven the compatibility of DES with the use of organometallic reagents such as organolithium or organomagnesium compounds (Vidal et al, 2014, 2016; García-Álvarez et al, 2015, 2018; Rodríguez-Álvarez et al, 2018), we decided to test the cross-coupling products 9b and 9c as substrates for the addition of different organometallic species in ChCl:ethyleneglycol as solvent. Aldehyde 9b could be reduced to the corresponding primary alcohol with NaBH 4 (Table 3, entry 1) or coupled with n -BuLi (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…In this context and during the last decade, a new family of sustainable reaction media, the socalled Deep Eutectic Solvents (DESs) (Abbott et al, 2003(Abbott et al, , 2004 has attracted the attention of many research groups worldwide. As consequence, these neoteric solvents have been broadly applied in chemistry as sustainable reaction media for: (i) polar organometallic chemistry (Mallardo et al, 2014;Vidal et al, 2014Vidal et al, , 2016Sassone et al, 2015;García-Álvarez et al, 2018;Rodríguez-Álvarez et al, 2018;Ghinato et al, 2019); (ii) metal catalyzed organic reactions (García-Álvarez, 2015; Vidal and García-Álvarez, 2019); (iii) biocatalysis (Gotor-Fernández and Paul, 2018); (iv) traditional organic synthesis (Liu et al, 2015;Alonso et al, 2016); (v) metal extraction and electrochemistry (Smith et al, 2014;Millia et al, 2018); and (v) polymer science (Carriazo et al, 2012;del Monte et al, 2014;Mota-Morales et al, 2018;Quirós-Montes et al, 2019;Roda et al, 2019;Sánchez-Condado et al, 2019). These sustainable eutectic solvents can be obtained just by mixing (without any further steps of purification or isolation) two molecules capable of forming a complex intermolecular network based on hydrogenbond interactions.…”
Section: Introductionmentioning
confidence: 99%